1990
DOI: 10.1093/ajcn/52.4.616
|View full text |Cite
|
Sign up to set email alerts
|

Consequences for maternal nutrition of reproductive stress across consecutive pregnancies

Abstract: Frequent cycles of reproduction increase the risk that lactation will overlap with pregnancy and shorten the duration of the recuperative interval (nonpregnant and nonlactating portion) within the reproductive cycle, thereby increasing the risk of maternal nutritional depletion. Nutritional responses to these stresses have been demonstrated by contrasting groups of women with different experiences; however, these relationships may be spurious and the result of third factors. In this study, responses to changin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 7 publications
0
41
0
Order By: Relevance
“…Merchant et al 7,8 reported that an overlap was associated with a nonsignificant decrease of 57 g in birth weight; the effect increased with the overlap duration. Studies with the appropriate design to look at birth outcomes (risk of low birth weight or prematurity) have not been conducted yet.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Merchant et al 7,8 reported that an overlap was associated with a nonsignificant decrease of 57 g in birth weight; the effect increased with the overlap duration. Studies with the appropriate design to look at birth outcomes (risk of low birth weight or prematurity) have not been conducted yet.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5] Despite this, the practice is common. 7,8,28,29 In Bangladesh, an estimated 20% of women who were lactating and pregnant were still lactating at the beginning of the ninth month. 28 In Guatemala, 50% of pregnant women were breastfeeding an older children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with greater numbers of births have been shown to suffer from additional health and nutritional complications (28) . Modern contraception use could also be a proxy for modernity and utilization of health services.…”
Section: Modern Contraceptivesmentioning
confidence: 99%
“…Maternal nutritional depletion might be impli- (Merchant et al 1990a;Merchant et al 1990b). Improving access to available reproductive health services (e.g.…”
Section: Discussionmentioning
confidence: 99%